Optimalisasi Kinerja Lembaga Halal Center Berbasis Total Quality Management (TQM): Studi Pada IAIN Kediri - Irfan Harmoko (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to examines the optimization of institutional performance at the Halal Center of IAIN Kediri through the implementation of Total Quality Management (TQM) focusing on four core Key Performance Indicators (KPIs): halal certification services, education and outreach, research and development, and management and governance. Using a qualitative case study approach, data were gathered through interviews, observations, and document analysis to capture an in-depth understanding of organizational processes before and after TQM implementation. The results show that TQM significantly improves the speed and accuracy of halal certification services, increases the number and competency of halal product assistants, and expands community education initiatives on halal awareness. Additionally, the approach stimulates research activities related to the halal ecosystem and strengthens institutional governance through better facilities, increased staff capacity, and the establishment of a more structured operational system. These findings empirically confirm that TQM principles—customer focus, continuous improvement, teamwork, and evidence-based decision-making—are highly relevant for halal certification institutions within higher education settings. The study contributes to the growing literature on quality management in the halal sector and highlights the importance of institutional commitment and cross-unit coordination for successful TQM implementation. Future initiatives should prioritize digitalization, auditor capacity-building, and the refinement of measurable performance standards to ensure long-term sustainability and competitiveness of halal institutions in Indonesia..